Price equalization does not imply free trade - Piyusha Mutreja; B. Ravikumar; Raymond Riezman; Michael J. Sposi (Center for Economic Studies and ifo Institute (CESifo), 2013)
In this paper we show that price equalization alone is not sufficient to determine the barriers to international trade. There are many barrier combinations that deliver price equalization, but each combination implies a different volume of trade. We demonstrate this first theoretically in a simple two-country model. We then demonstrate the result quantitatively for the case of capital goods trade: barriers have to be large in order to be consistent with the observed trade flows even though our model implies that capital goods prices are similar across countries. Zero barriers to trade in capital goods will deliver price equalization in capital goods, but cannot reproduce the observed trade flows.
Keywords: F01; F02; 330; international trade; capital goods trade; Internationaler Preiszusammenhang; Außenwirtschaftstheorie; Markteintritt; Zwei-Länder-Modell; Theorie; Investitionsgut; Preis; Außenhandel; Schätzung; Welt